FHL3 Contributes to EMT and Chemotherapy Resistance Through Up-Regulation of Slug and Activation of TGFβ/Smad-Independent Pathways in Gastric Cancer - Cao, Guodong; Li, Pengping; He, Xiaobo; Jin, Mengyao; Li, Mengying; Chen, Sihan; Xu, Xin; Sun, Qiang; Xiong, Maoming; Chen, Bo (Frontiers in Oncology, 2021)
Background: Gastric cancer presents high risk of metastasis and chemotherapy resistance. Hence, the mechanistic understanding of the tumor metastasis and chemotherapy resistance is quitely important. Methods: TCGA database and clinical samples are used for exploring the role of FHL3 in disease progression and prognosis. The roles of FHL3 in metastasis and chemotherapy resistance are explored in vitro and in vivo by siRNA or shRNA treatment. Finally, we explore the FHL3-mediated EMT and chemotherapy resistance. Results: mRNA and protein level of FHL3 is significantly up-regulated in gastric cancer tissues when compares with it in adjacent tissue. Higher expression level of FHL3 companies with worse overall survival in gastric cancer. OPH resistance cells show higher level of FHL3 and mesenchymal phenotype. Knockdown of FHL3 slightly inhibits the cell growth, while it obviously sensitizes the chemotherapy in vivo and in vitro. In addition, down-regulation of FHL3 decreases the mesenchymal markers, such as Slug, Snail, Twist1, and vimentin, while increases the epithelial marker E-cadherin. For mechanism study, FHL3 knockdown down-regulates the expression level or activity of MAPK/ERK pathway and TGFβ/PI3K/Akt/GSK3β-RNF146/ubiquitin pathway in OPH resistance cells. Mesenchymal phenotype cells hold higher level of MDR1, and the FHL3 knockdown reverts the MDR1 in this type cell. Conclusion: FHL3 is a risk of disease progression in gastric cancer. MAPK and PI3K pathways were activated when FHL3 induces EMT and drug resistance process, but the TGFβ/Smad -dependent pathway did not participate in the process. FHL3 competitively bond the ubiquitin complex (slug/GSK3β/RNF146) with slug, inhibit ubiquitination of Slug.